Pengaruh Motivasi Belajar Dan Persepsi Atas Kompetensi Guru Terhadap Prestasi Belajar Ilmu Pengetahuan Sosial - Tita Tresnawati (Herodotus: Jurnal Pendidikan IPS, 2018)
This study aims to determine the influence of learning motivation and perceptions of teacher competence on social science learning achievement. The research used quantitative approach with survey method. The number of samples is 80 people through simple random sampling. Multiple regression analysis technique is used to analyze data by using SPSS Ver application. 22 for Window. The results of the study prove There is a significant influence of learning motivation and perceptions of the competence of teachers collectively on social science learning achievements in SMPN Kabupaten Lebak. There is a significant influence of learning motivation on social studies achievement in SMPN Kabupaten Lebak. There is a significant influence perceptions on teacher competence on Social Science learning achievement in SMPN Kabupaten Lebak.